Cointegration and Tests of Purchasing Power Parity - Corbae, Dean; Ouliaris, Sam (The Review of Economics and Statistics, 1988)
Nonstationarity in the levels of spot exchange rates and domestic and foreign price indices makes the use of conventional tests of the absolute version of purchasing power parity (PPP) inappropriate. If PPP is true, inter-country commodity arbitrage ensures that deviations from a linear combination of spot exchange rates and domestic and foreign price levels should be stationary. Under these conditions, exchange rates and price levels should form a cointegrated system. We find the null hypothesis of no cointegration cannot be rejected for all five countries, thus violating the long-run absolute version of PPP.